"I feel like I'm being stabbed by a thousand tiny men": The challenges of communicating endometriosis pain. (September 2020) - Bullo, Stella
Endometriosis, as a widespread gynecological condition, affects an estimated 1 in 10 women and yet has a worldwide average diagnosis length of 7.5 years. Causing incapacitating pain, among other associated manifestations, the condition severely impacts on women's lives. This article uses online survey data to investigate how pre-diagnosis endometriosis pain is conceptualized and articulated in order to explore communication challenges reported in early consultations that can potentially be seen to play a role in diagnosis delay. The findings of this study indicate that women feel that they do not have the appropriate tools to describe their pain and, in many instances, feel dismissed therefore prolonging diagnosis. The article finds that the majority of the pain descriptors identified use elaborate metaphorical scenarios to convey the intensity of the pain and concludes with some reflections on the issue of metaphorical language in endometriosis pain communication practices while calling for interdisciplinary work in order to devise appropriate tools for endometriosis pain communication.